2014
DOI: 10.1681/asn.2013070791
|View full text |Cite
|
Sign up to set email alerts
|

Renal Cortical Pyruvate Depletion during AKI

Abstract: Pyruvate is a key intermediary in energy metabolism and can exert antioxidant and anti-inflammatory effects. However, the fate of pyruvate during AKI remains unknown. Here, we assessed renal cortical pyruvate and its major determinants (glycolysis, gluconeogenesis, pyruvate dehydrogenase [PDH], and H 2 O 2 levels) in mice subjected to unilateral ischemia (15-60 minutes; 0-18 hours of vascular reflow) or glycerol-induced ARF. The fate of postischemic lactate, which can be converted back to pyruvate by lactate d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
64
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(72 citation statements)
references
References 28 publications
6
64
1
1
Order By: Relevance
“…These findings are in agreement with recent reports of renal cortical pyruvate depletion in both I/R and glycerolinduced AKI in mice (75). The same study also reported glycolytic induction in the renal cortex only occurs during the ischemic period and is reversed after reperfusion (75). However, it should be noted that some of the analyses performed here, including pyruvate and lactate measurements, are not sufficiently powered to detect small changes between groups.…”
Section: F440supporting
confidence: 93%
See 3 more Smart Citations
“…These findings are in agreement with recent reports of renal cortical pyruvate depletion in both I/R and glycerolinduced AKI in mice (75). The same study also reported glycolytic induction in the renal cortex only occurs during the ischemic period and is reversed after reperfusion (75). However, it should be noted that some of the analyses performed here, including pyruvate and lactate measurements, are not sufficiently powered to detect small changes between groups.…”
Section: F440supporting
confidence: 93%
“…Pyruvate content was decreased approximately twofold at both 3 and 18 h, whereas lactate levels trended toward a decrease at 3 h but returned to baseline levels by 18 h post-LPS. These findings are in agreement with recent reports of renal cortical pyruvate depletion in both I/R and glycerolinduced AKI in mice (75). The same study also reported glycolytic induction in the renal cortex only occurs during the ischemic period and is reversed after reperfusion (75).…”
Section: F440supporting
confidence: 93%
See 2 more Smart Citations
“…Historical interpretation of studies from heterogeneous ex vivo preparations suggests that glucose utilization for glycolysis by the proximal tubule is minimal (17, 32). However, recent studies suggest that proximal tubule glycolytic flux plays an important role under various stressors and in diverse pathophysiological conditions (14,15,24,34). Nonetheless, a detailed examination and understanding of kidney glucose metabolism in vivo is lacking in large extent to the absence of tools to examine this process in vivo.…”
mentioning
confidence: 99%